(untitled) (Research, Society and Development, 2022)
Objective: To carry out a brief literature review, highlighting botanical, phytochemical and pharmacological activities, especially antibacterial, of M. chamomilla. Methodology: A narrative literature review was carried out, based on the data present in the platforms: Latin American and Caribbean Literature in Health Sciences (LILACS), BVS – Virtual Health Library, Electronic Library Scientific Electronic Library Online (SciELO) and academic Google. Inclusion criteria were: research aimed at the herbal use of Matricaria chamomilla, published in English, Portuguese or Spanish; in the format of articles, reviews, dissertations and theses in the period from 2015 to 2021. Then there was the grouping and synthesis of the themes, presenting the knowledge in detail about the proposed theme. Results: Based on the results, M. chamomilla has a great biological potential due to its phytochemical components, such as terpenes, examples being camazulene and bisabolol, responsible for the anti-inflammatory and antiproliferative activity. Regarding the antibacterial activity, studies show that it becomes greater when there is an association of antibiotics with the essential oil. Conclusion: Based on the literature review of Matricaria chamomilla, the relevance of its medicinal use, mainly as a natural antibacterial agent, is reinforced.